Three-dimensional ultrasound and 3D Power Angio in the diagnostics of ovarian neoplasms - Dańska, Anna; Bidziński, Mariusz (Menopause Review/Przegląd Menopauzalny, 2004)
Summary The 3D ultrasound and Power Angio techniques are the latest developments in medical tomography and ultrasonography. The application spectrum and experiences are encouraging in different fields of medicine, also in gynecology, obstetrics and gynecologic oncology. This article presents the role and achievements of conventional 2D ultrasound in early detection and diagnosis of ovarian cancer; the benefits of 3D ultrasound and Power Angio comparing to 2D US have also been presented. The newer technique, as more accurate, seems to be a promising tool increasing the number of earlier detected malignant ovarian neoplasms. Not only benefits but also some limitations of 3D ultrasound and Power Doppler have been mentioned as well as the future perspectives of this fascinating method.